CHANGES TO THE CONCEPTION OF GEOGRAPHY CURRICULA WITHIN UNIVERSITY EDUCATION IN POLAND IN THE 21ST CENTURY IN THE FACE OF LABOUR MARKET CHALLENGES∗ - Danuta PIROG (European Journal of Geography)
In the nineties of the 20th century, there was a rapid growth in the number of applicants for Polish universities. Unfortunately, this favourable situation didn’t cause any structural or curriculum changes. Traditional geography curriculum remained obsolete and not adapted to the challenging Polish labour market. Since the beginning of the 21st century, the situation has started to change mainly due to the baby boom, which has caused a general fall in the number of people who want to study. This fact compelled academic authorities to think over the concept of geographic education and to conduct reforms. Another factor that forced changes was the obligation to implement the Bologna Declaration after Poland entered the EU in 2004. This paper presents the analysis of the evolution of the conception of geography in higher education in years 2002-2012, as well as it assesses both positive and negative aspects of the current geography academic education programmes in Poland, taking into consideration the improvement in the quality of education, fair measurement and assessment of this quality and analysis of labour market needs with reference to the future graduates of geography studies. In order to achieve the objective of this study, the method of document analysis has been used. The analysis includes geography education standards and curricula from all universities that provide geography education. Moreover, the study includes diagnostic surveys conducted among students on the change of their level of satisfaction from the geography studies and specialities that they have chosen at the end of studies and approx. half a year after completion of studies, i.e. during their transition to the labour market.